Outside [NOW] : Workshop interdisciplinaire. - Dreessen, Brice; Ungaro, Géraldine; Salinas, Pauline (s.l. : Éditions Les Brasseurs, 2018)
Achkar, Charlotte ; Anezo, Caroline ; Arseni, Konstantina ; Cremers, Merel ; de Laforêt, Anita ; De Meirleir, Niels ; Devriendt, Ruth ; Klasen, Malsy ; Kriaa, Gauthier ; Locquet, Mathieu ; Stehling, Julia ; Thys, Déborah ; Capsule Biohardcore ; Cattelain, Claude ; Coëllier, Sylvie ; De Winter, Jonathan ; Fortino, André ; Gandolphe, Romain ; Van Cauteren, Philippe ; Brunello, Baptiste ; Gillain, Céline ; Loze, Ariane ; Schmitt, Mathieu
Ouside [NOW], Les Brasseurs, Liège, 4 au 14 avril 2018
boek